Efektivitas Blended-Problem Based Learning dengan Lesson Study Terhadap Hasil Belajar - Triyanto, Samuel Agus; Prabowo, Chandra Adi (Bioedukasi: Jurnal Pendidikan Biologi, 2020)
The effectiveness of learning is important to know, as an indicator that learning created has brought useful results for students or educators. The purpose of this study is to describe the effectiveness of Blended-Problem Based Learning models with Lesson Study toward cognitive learning outcomes. The effectiveness of learning toward cognitive learning outcomes was obtained through cognitive tests, interview and observation guidlines, then the results analyzed by a qualitative approach. The research data shows that the average cognitive learning outcomes of students in Class X IPA 7 of SMA Negeri 1 Karanganyar in the 2015/2016 Academic Year increased by 7,27% and students also have a good response to learning. These results indicate that the Blended-Problem Based Learning model with Lesson Study effectively improves cognitive learning outcomes, with students experiencing learning activities from the best efforts of educators in creating learning.